Cannabis and schizophrenia spectrum disorders: a review of clinical studies - Rodrigo, C.; Rajapakse, S. (My University, 2009)
Cannabis is the most widely used illegitimate substance in the world, and the number of users has increased by 10% over the last decade worldwide. Therefore, it is important to review the evidence on psychoactive properties of cannabis and its possible association with schizophrenia spectrum disorders (SSD). We searched MEDLINE with the key words cannabis and schizophrenia. The search was limited to articles published in English over the last 10 years (1999-2009). Bibliographies of cited literature were also searched. Data sources included reviews published in core clinical journals, cohort studies, interventional studies, case-control studies, cross-sectional analyses and epidemiological data. Results are discussed under 2 topics. Firstly, evidence related to biochemical functioning of cannabinoids and their relationship to endocannabinoid system is discussed briefly. Secondly, the evidence from clinical studies on cannabis, psychosis proneness and SSD are discussed in detail. The discussion is structured to fit in the evidence from results section to 3 plausible hypotheses on cannabis use and SSD. The evidence for and against each hypothesis is discussed. Despite new evidence, the exact relationship between cannabis and SSD is unclear. There is no firm evidence that cannabis causes SSD. The evidence for the argument that schizophrenic patients are attracted to cannabis is also not strong. The most plausible explanation is that cannabis use and psychosis proneness may have synergistic effects in a vulnerable minority.